Circulating Platelets Show Increased Activation in Patients with Acute Cerebral Ischemia - Zeller, Joern A.; Tschoepe, Diethelm; Kessler, Christof (Thrombosis and Haemostasis, 1999)
Platelet activation plays a central role in acute arterial stenosis as has been shown in coronary heart disease. Likewise it can be assumed to be of importance in the evolution of acute cerebral ischemia (ACI), particularly in patients with large vessel disease. Flow cytometric detection of platelet adhesion molecules as a marker of platelet activation in a group of patients with ACI and different etiologies has not been evaluated. In 72 patients with ACI and 72 controls, the exposure of activation-dependent adhesion molecules was determined using flow cytometry after immunostaining with monoclonal antibodies against CD 62, CD 63 and thrombospondin. The extent of platelet activation differed as a function of the etiology of ACI: platelets from patients with atherosclerosis of brain-supplying arteries expressed significantly more activation markers than did controls, whereas patients with cardioembolic stroke did not. By analyzing platelet adhesion molecules it is possible to describe platelet activation profiles in patients with acute cerebral ischemia. This diagnostic procedure will be useful for monitoring individualized anti-platelet therapy and may enable distinguishing different subgroups of stroke patients.